DEVELOPMENT AND CONTRIBUTION OF OPEN SOURCE SOFTWARE COMMUNITIES FOR THE LIBRARY PROGRESS IN INDONESIA - Fakhlina, Resty Jayanti; Saputra, Dwi Fajar (Record and Library Journal, 2019)
Background of the study: Open source software is an open-based software and can be accessed for free. This open source software is growing rapidly at domestic and overseas. Many criteria are used by users. In this case, the library Also, choosing the open source software they need. There are several organization that a accommodate Review these users of open source software in Indonesia. Some of the open source software is the Slims organizes community and Surabaya's Linux Community.Purpose: The purpose of this study was to determine the development and contribution of the community to libraries in Indonesia.Method: The method used is a qualitative method with a descriptive approach.Findings: The results of this study are the Open Source Community the which plays an important role in the progress of libraries in Indonesia, this can be seen from the number of school libraries that have implemented an IT in providing services to users by using open source software.Conclusion: The conclusion is the development and contribution of the Open Source Community in Indonesia is needed for the progress of the library in the future.